Pengaruh terapi kognitif terhadap harga diri remaja korban bullying - Andreansyach, Dwiky Andreansyach; Abdul Rokhman; Arifal Aris (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Bullying in Islamic boarding school environments has a significant impact on adolescents' self-esteem, potentially resulting in long-term psychological disorders if not handled properly. Purpose: To analyze the effect of cognitive therapy on the self-esteem of adolescent victims of bullying. Method: Nonequivalent Control Group Design, this study involved 60 adolescent respondents selected through purposive sampling and divided into treatment groups (cognitive therapy) and control groups (health counseling). Data collection using Rosenberg's Self-esteem Scale was conducted before and after the intervention. Results: Before the intervention, the majority of respondents in the control group experienced low self-esteem (80.0%), while the treatment group had a diverse distribution of self-esteem. After the intervention, there was a significant increase in the treatment group with the majority achieving high self-esteem (63.3%), while the control group was still dominated by the low self-esteem category (50.0%). Independent Sample T-Test analysis proved a significant effect of cognitive therapy on increasing the self-esteem of adolescent victims of bullying (p = 0.001). Conclusion: Cognitive therapy is effective in helping adolescents identify and change negative thought patterns into positive ones, so it can be recommended as an intervention of choice to address the psychological impact of bullying on adolescents in Islamic boarding school environments. Keywords: Adolescents; Bullying; Cocnitive Therapy; Islamic Boarding School; Self Esteem. Pendahuluan: Bullying di lingkungan pesantren memiliki dampak signifikan terhadap harga diri remaja, berpotensi mengakibatkan gangguan psikologis jangka panjang jika tidak ditangani secara tepat. Tujuan: Untuk menganalisis pengaruh terapi kognitif terhadap harga diri remaja korban bullying. Metode: Desain Nonequivalent Control Group, penelitian ini melibatkan 60 responden remaja yang dipilih melalui purposive sampling dan dibagi dalam kelompok perlakuan (terapi kognitif) dan kelompok kontrol (penyuluhan kesehatan). Pengumpulan data menggunakan Rosenberg's Self-esteem Scale dilakukan sebelum dan sesudah intervensi. Hasil: Sebelum intervensi, mayoritas responden kelompok kontrol mengalami harga diri rendah (80.0%), sementara kelompok perlakuan memiliki distribusi harga diri yang beragam. Setelah intervensi, terjadi peningkatan signifikan pada kelompok perlakuan dengan mayoritas mencapai harga diri tinggi (63.3%), sedangkan kelompok kontrol masih didominasi kategori harga diri rendah (50.0%). Analisis Independent Sample T-Test membuktikan adanya pengaruh signifikan terapi kognitif terhadap peningkatan harga diri remaja korban bullying (p=0.001). Simpulan: Terapi kognitif efektif membantu remaja mengidentifikasi dan mengubah pola pikir negatif menjadi positif, sehingga dapat direkomendasikan sebagai intervensi pilihan untuk mengatasi dampak psikologis bullying pada remaja di lingkungan pesantren. Kata kunci: Bullying; Harga Diri; Pesantren; Remaja; Terapi Kognitif.